SEJARAH HUBUNGAN MALAYAPURA DENGAN KERAJAAN PANAI PADA TAHUN 1347-1375 MASEHI - Hana Nur Azizah; Bedriati Ibrahim; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the history of the relationship between Malaysiaand the Kingdom of Panai in the dimensions of the bilateral diplomatic relationsbetween the two regions. This research has research goals including explaining thehistory of Malayapura, the condition of Malayapura during Adiyawarman's reign, therelationship of Malayapura in the economic, political and religious spheres. Theresearch method used in the research is the historical research method which uses datacollection techniques in the form of literature and documentation. This relationship willaffect the realization of common goals and interests in developing political, economicactivities and even the style of religion. From the political aspect, it can be seen that thePanai kingdom and its nature have a lot of wealth such as gold, frankincense andcamphor, an economic capital that becomes the stimulus for mining commodities tradefor the needs needed in the political field. Panai has a reference as one of the importantareas for Malayapura in terms of economic interaction based on the wealthMalayapura needs. With the natural wealth that Panai possesses, it has attracted othercountries to come and stop in Panai. From the religious aspect, Malayapura hasinfluenced the religious view in Panai, as evidenced by the legacy of the temple complexin Panai. This influence was possible geographically because of the baths at Panai(sign) and Malayapura. In this case, Panai and Malayapura are believed to adhere toBuddhism with Tantric teachings.Key Words: Relationship, Malayapura, Kingdom of Panai